On the issue of protecting labor rights of minors in Omsk in early 1920’s - T. V. Glazunova (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the work carried out in the USSR on child labor protection in the early 1920’s on the example of Omsk. The connection of the studied issue with the historiography of the problem is given. In the context of the legislative framework affecting the work of adolescents and the work of supervisory authorities, the problems faced by minors when applying for work are studied, the difficulties of the situation of children in Omsk are outlined, where one of the solutions to improve their situation was assistance in finding employment. The work of Omsk labor protection inspectors is studied using specific examples. The publication is addressed to researchers of everyday life, the history of labor relations and childhood in Western Siberia in the early 1920’s.